Effect of Dry Extracts of Medicinal Plants on Urinary Excretion and Ion Exchange - G. Yu., Djanaev; Sh. M., Makhsumov; O. A., Zaytseva; Kh. I., Khudayberdiev; O. O., Askarov (PT. Antis International Publisher, 2024)
According to the results of an experimental scientific study, in relatively small doses of dry extracts of the studied plants (100 μg/kg + 50 mg/kg), the average urinary excretion was 61.9% compared to the control group, and in large doses (250 μg + 100 mg/kg) was found to increase by 73.8%. Therefore, when plant extracts are used in the studied doses, their effect on urine excretion remains at full blood level.